Cyto- and genotoxicity of a vanadyl(IV) complex with oxodiacetate in human colon adenocarcinoma (Caco-2) cells: potential use in cancer therapy - Di Virgilio, Ana Laura (2011)
The complex of vanadyl(IV) cation with oxodiacetate, VO(oda) caused an inhibitory effect on the proliferation of the human colon adenocarcinoma cell line Caco-2 in the range of 25–100 μM (P < 0.001). This inhibition was partially reversed by scavengers of free radicals. The difference in cell proliferation in the presence and the absence of scavengers was statistically significant in the range of 50–100 μM (P < 0.05). VO(oda) altered lysosomal and mitochondria metabolisms (neutral red and MTT bioassays) in a dose–response manner from 10 μM (P < 0.001). Morphological studies showed important transformations that correlated with the disassembly of actin filaments and a decrease in the number of cells in a dose response manner. Moreover, VO(oda) caused statistically significant genotoxic effects on Caco-2 cells in the low range of concentration (5–25 μM) (Comet assay). Increment in the oxidative stress and a decrease in the GSH level are the main cytotoxic mechanisms of VO(oda). These effects were partially reversed by scavengers of free radicals in the range of 50–100 μM (P < 0.05). Besides, VO(oda) interacted with plasmidic DNA causing single and double strand cleavage, probably through the action of free radical species. Altogether, these results suggest that VO(oda) is a good candidate to be evaluated for alternative therapeutics in cancer treatment.